Hepascore predicts liver outcomes and all‐cause mortality in long‐term methotrexate users: A retrospective cohort study. Issue 6 (21st October 2020) - Wang, Zhengyi; Huang, Yi; Nossent, Hans; Chan, Jonathan J; Adams, Leon A; Joseph, John; Cheng, Wendy; Garas, George; MacQuillan, Gerry; Jeffrey, Gary P
Abstract: Background and aim: Methotrexate (MTX) is routinely used for immunological disorders, and its long‐term use is associated with hepatotoxicity. The aim of this study was to investigate whether a serum liver fibrosis test (Hepascore) predicted the risk of adverse liver‐related outcomes and mortality. Methods: A total of 92 patients in Western Australia who had a long‐term MTX intake history, from 2004 to 2016, were recruited and followed up from the first Hepascore to death or end of the study. Clinical data, all deaths, and liver‐related outcomes (liver‐related death and decompensation) were obtained from hospital, PathWest, and WA Data Linkage Unit databases. Results: Nine deaths and four adverse liver‐related outcomes occurred during the follow up of 354 person‐years. The 5‐year survival was 86.1%. The liver‐related outcome free survival was 95.6%. Baseline Hepascore ≥0.84 was associated with advanced fibrosis on liver biopsy ( P = 0.025). A baseline Hepascore ≥0.84 was significantly associated with higher risks for adverse liver‐related outcomes ( P  < 0.001) and all‐cause mortality ( P = 0.001). Cox regression demonstrated that only baseline Hepascore ≥0.84 was independently associated with the increased risk of all‐cause mortality (7.91 [1.52–41.29], P = 0.014). Moreover, any Hepascore ≥0.84 found during follow up was independently associated with the increased risk of all‐cause mortality (86.18 [4.03–1844.83], P = 0.007). Conclusions: This study demonstrated the potential importance of Hepascore monitoring in long‐term MTX users. Patients with a Hepascore higher than 0.84 at any stage had increased mortality, but further studies are required to confirm this finding. Abstract : Hepascore, a serum liver fibrosis test, predicted the risk of adverse liver‐related outcomes and mortality in long‐term MTX users. Patients with a Hepascore higher than 0.84 at any stage should be advised to stop MTX to prevent further liver decompensation or death.